2000
DOI: 10.1053/euhj.1999.1851
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial mapping of atrial fibrillation in the human right atrium using a non-contact catheter

Abstract: Background Endocardial mapping of atrial fibrillation in humans is limited by its low resolution and by complexities in the arrhythmia and atrial anatomy. Methods and ResultsA catheter mounted non-contact multielectrode was deployed in the right atrium of 11 patients with atrial fibrillation and used to reconstruct 3360 electrograms, superimposed onto a computer-simulated model of the endocardium, using inverse solution mathematics. This allows construction of isopotential maps of the right atrium. Patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 36 publications
3
64
0
1
Order By: Relevance
“…13 Although epicardial mapping has been used extensively to assess atrial activation both in animals and intraoperatively in humans, 14 -17 access to the interatrial septum and the posterior atria between the caval and pulmonary veins has prevented complete epicardial mapping 17 and general anesthesia may influence conduction. 18 Recent publications have shown that left-to-right interatrial conduction occurs predominantly through Bachmann's bundle, 19,20 and we have previously shown that during AF, after periods of electrical silence, the RA consistently reactivates from the region of Bachmann's bundle, sometimes with additional breakthrough at the CS ostium or oval fossa. 20 Despite the difficulties in left atrial mapping noted above, the predominantly epicardial studies of LA activation 15,17 have suggested that the principal route of epicardial LA activation during SR is through Bachmann's bundle, although this was not a universal finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although epicardial mapping has been used extensively to assess atrial activation both in animals and intraoperatively in humans, 14 -17 access to the interatrial septum and the posterior atria between the caval and pulmonary veins has prevented complete epicardial mapping 17 and general anesthesia may influence conduction. 18 Recent publications have shown that left-to-right interatrial conduction occurs predominantly through Bachmann's bundle, 19,20 and we have previously shown that during AF, after periods of electrical silence, the RA consistently reactivates from the region of Bachmann's bundle, sometimes with additional breakthrough at the CS ostium or oval fossa. 20 Despite the difficulties in left atrial mapping noted above, the predominantly epicardial studies of LA activation 15,17 have suggested that the principal route of epicardial LA activation during SR is through Bachmann's bundle, although this was not a universal finding.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recent publications have shown that left-to-right interatrial conduction occurs predominantly through Bachmann's bundle, 19,20 and we have previously shown that during AF, after periods of electrical silence, the RA consistently reactivates from the region of Bachmann's bundle, sometimes with additional breakthrough at the CS ostium or oval fossa. 20 Despite the difficulties in left atrial mapping noted above, the predominantly epicardial studies of LA activation 15,17 have suggested that the principal route of epicardial LA activation during SR is through Bachmann's bundle, although this was not a universal finding. 14,16 A recent study also identified posteroseptal pathways involved in SR activation of the LA endocardium.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] The accuracy of reconstructed electrograms is decreased at a distance >40 mm from the center of the array, particularly during AF. 22 In the present study group of AF patients, the average parasternal long-axis LA diameter was only 41±6 mm on transthoracic echocardiography.…”
Section: Study Limitationsmentioning
confidence: 99%
“…AF is generally considered to be maintained by multiple re-entrant wavelets of excitation that propagate in different directions around the atrial myocardium [26,27]. The maintenance of AF seems to depend on the presence of a sufficient number of small wavefronts while undergoing fractionation, collisions and coalescence over the atrial surface.…”
Section: Self-limited Vs Self-sustained Atrial Fibrillationmentioning
confidence: 99%